Rhodopsin: A Potential Biomarker for Neurodegenerative Diseases - Lenahan, Cameron; Sanghavi, Rajvee; Huang, Lei; Zhang, John H. (Frontiers in Neuroscience, 2020)
Retinal alterations have recently been associated with numerous neurodegenerative diseases. Rhodopsin is a G-protein coupled receptor found in the rod cells of the retina. As a biomarker associated with retinal thinning and degeneration, it bears potential in the early detection and monitoring of several neurodegenerative diseases. In this review article, we summarize the findings of correlations between rhodopsin and several neurodegenerative disorders as well as the potential of a novel technique, cSLO, in the quantification of rhodopsin.